Depression in Primary Caretakers of Maintenance Hemodialysis Patients - Natasha Khatri, Kiran Nasir, Ruqaya Qureshi, Murtaza Dhrolia, Aasim Ahmad (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the frequency of depression among the primary caretakers of maintenance hemodialysis (MHD) patients at our center and its association with different factors. Study Design: Prospective cross-sectional study. Place and Duration of Study: The Kidney Centre Postgraduate Training Institute Karachi, Pakistan from 1st July 2021 to 31st December 2021. Methodology: One hundred and eighty-five data were collected using two questionnaires, one for demographic data and other was Beck Depression Inventory (BDI-II) for assessment of depression, filled by the primary investigator and caretaker respectively. BD-II is a self-reporting questionnaire that consists of 21 questions and is used globally for measuring the severity of depression. Results: There were 123 (66.5%) males and 62 (33.5%) females. The mean age was 44.8±12.4 years. Hypertension was the most prevalent comorbid in 56 (30.3%) followed by diabetes mellitus in 32 (17.3%). The most common relationship was children of the patient in 59 (31.9%), whereas the second most common relationship was a spouse in 54 (29.2%). We found that 99 (53.5%) of our study participants had minimal depression, while none had severe depression. Variables like education, work status, monthly income, number of earning people, years on hemodialysis, comorbid conditions, and relationship with the patients were significantly associated with the degree of depression (P<0.05). Conclusion: The participants were suffering from minimal depression. We also found a positive association of depression in caretakers with multiple study variables. These findings will help physicians identify depression in caretakers of maintenance hemodialysis patients and identify those who need a referral to a psychiatrist/psychologist for proper treatment. Keywords: Depression, Primary Caretaker, maintenance, Hemodialysis